New records of Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) and Tetranychus urticae Koch (Acari: Tetranychidae) in strawberries crops in Venezuela - Solano-Rojas, Yohan Alexander; Giménez, Aracelis; Pérez de Camacaro, María; Morales-Sánchez, José; Zurita, Gustavo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
In order to observe species of thrips and mites found in commercial strawberry crops in Venezuela, studies were conducted in Bailadores (Mérida State), Cabimbú (Trujillo State), La Colonia Tovar (Aragua State), Cubiro, Paso Real, Páramo Abajo and Tarabana (Lara State). We examined leaf buds, leaves, flower buds, flowers and fruits in the field in order to collect immature and adult thrips/mites in strawberry cultivars. Then, thrips and mites in the immature stage were reared in a laboratory until adults emerged. Specimens were pinned, tagged and deposited at the Museum of Entomology José M. Osorio (MJMO) collection at the Universidad Centroccidental “Lisandro Alvarado” (UCLA). In the taxonomic review, it was possible to identify the species Frankliniella occidentalis (Pergande) and Tetranychus urticae Koch. This is the first report of these species in strawberry crops in Venezuela.